Don't burn our bridges : the case for owning airlines - Holder, Jean S. (UWI Press KingstonJM, 2010)
Examines the critical importance of air transportation, its role as a bridge between the countries of the Caribbean and the external world and between the countries themselves; in a region which is heavily dependent on tourism and separated from each by distances of water which cannot be easily or quickly traversed by small boats.